DNA sequencing data in MDS-patients treated with allogeneic transplantation - Yoshizato, Tetsuichi; Jacobsen, Sten Eirik (Karolinska Institutet, 2023)
The deposited data consists of 47 bam files for targeted DNA sequencing and somatic mutation list called by bulk whole-genome sequencing in patients with myelodysplastic syndromes or related myeloid malignancies who received allogeneic stem cell transplantation. The objective of this data collection was to assess whether somatic mutation can be a marker for detecting early relapse. DNA sequencing was performed to identify somatic mutation candidates using samples collected at diagnosis and also performed for the comparison of the sensitivity of detection between digital droplet PCR and next-generation sequencing. We used three different gene panels for targeted DNA sequencing and the gene lists can be found in the cited Blood paper. Read alignment was performed against the GRCh37. In two patients in whom no recurrent driver mutations were identified, whole genome sequencing was performed. After alignment to GRCh37, somatic mutations were called using Genomon2, and identified somatic mutation list was deposited.

The total size of the deposited data is approximately 25 GB (24586652781 bytes).

Datasetet består av 47 bam-filer för målinriktad DNA-sekvensering och lista över somatiska mutationer som definierade via bulk helgenomsekvensering av patienter med myelodysplastiskt syndrom eller relaterade myeloida maligniteter som fått allogen stamcellstransplantation. Syftet med datainsamlingen var att utvärdera om somatiska mutationer kan vara en markör för att upptäcka tidigt återfall. DNA-sekvensering utfördes på prover som samlats in vid diagnos för att identifiera potentiella somatiska mutationer som sedan kunde följas i fler prover över tid. Data användes även för att jämföra sensitiviteten för detektion av mutationer mellan digital droplet-PCR och next generation sequencing. Vi använde tre olika genpaneler för målinriktad DNA-sekvensering och genlistorna kan hittas i den citerade artikeln, accepterad för publikation i Blood. DNA-fragment matchades mot referensgenomet, GRCh37. Hos två patienter där vi inte identifierade några sjukdomsorsakande mutationer, utfördes sekvensering av hela genomet. Efter anpassning till GRCh37 definierades somatiska mutationer med Genomon2, och den identifierade somatiska mutationslistan laddades upp.

Totala storleken för datasetet är ca 25 GB (24586652781 bytes).
DNA-sekvenseringsdata för MDS patienter behandlade med allogen transplantation
Keywords: Hematopoietic Stem Cells; Blodstamceller; Hematopoietic Stem Cell Transplantation; Blodstamcellstransplantation; Myelodysplastic syndromes; Myelodysplastiska syndrom; Medical and Health Sciences; Medicin och hälsovetenskap; Medical Genetics and Genomics; Medicinsk genetik och genomik; Cell and Molecular Biology; Cell- och molekylärbiologi; Hematology; Hematologi; Cancer and Oncology; Cancer och onkologi